Knowing me, imagining you: Projection and overbidding in auctions - Yves Breitmoser (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
People overestimate the probability that others share their values or preferences. I introduce type projection equilibrium (TPE) to capture such projection in Bayesian games. TPE allows each player to believe his opponents share his type with intermediate probability ρ. After establishing existence, I address my main question: How does projection affect behavior in games? I analyze auctions and distribution games. In auctions, projection implies an increased sense of competition, which induces overbidding in all (first-price) auctions. In addition, it biases the perceived value distribution, which induces cursed bidding in common value auctions. Thus, projection induces a hitherto neglected bias in bidding. It is novel in that it explains behavior across conditions and it is independently founded in psychology. I test projection equilibrium in multiple ways on existing data and find that it substantially improves on alternative concepts, both in isolation and in addition to them. The findings are cross-validated by testing projection of social preferences in distribution games.
Keywords: C72; C91; D44; 330